Caracaraí-RR: o rio e a cidade - uma paisagem modificada - Dias, Ana Paula Reis Santos (2017)
Historically, cities that were born on the banks of rivers appropriated the natural environment and transformed their landscape over time, by inserting and / or eliminating elements to meet the demand of population growth in these areas. The objective of this research was to understand the dynamics of the transformation of the landscape of the right bank of the Rio Branco into the urban perimeter of the city of Caracaraí (RR) through a multitemporal analysis (1986 to 2016). For this, the study was based on a descriptive research of a qualitative nature, with a historical approach, guided by qualitative methods, among which the observation and field research were highlighted. Field observations together with data from studies carried out by the Brazilian Institute of Geography and Statistics in 2005, gave rise to the charts and maps exposed in the course of the study. Bibliographical, iconographic and documentary material was also used, from books, magazines, printed or electronic documents. In addition, during the field visits, iconographic materials were collected from the personal collection of former residents of the area. In general, with the present approach it was realized that a series of human actions developed within the research area generated significant environmental impacts, contributing to the establishment of a transformed landscape, which was presented as a product of the occupation and exploitation of the natural environment. As there was a population overload in this alluvial plain, one has to eliminate (the vegetation) or the addition of new elements (the leisure) in the landscape, making it uncharacterized of its originality. The results show that the environmental changes occurred, were amplified over the 30 years analyzed in the research, occurring in a gradual and punctual way. Therefore, the present study verified that the landscape established in the right margin of the White river in the urban perimeter of the city of Caracaraí is fruit of its process of population.